Tactical or strategic modelling of freight transport logistics in a meso-economic framework - Holmblad, Mikal (Proceedings from the Annual Transport Conference at Aalborg University, 2004)
The paper describes a freight transport model that computes a regional transport flow pattern (OD-matrix) from a trade flow structure (PC-matrix). Two important features of the model are the use of regional transport centers in the transport chain bulding, and a representation of assumed large-scale operational advantages of transport agents operating in a transport logistics system.